Makna Dupa Dalam Tradisi Ziarah Makam Sunan Gunung Jati Cirebon, Jawa Barat - Syaripulloh; Tanggok, Ikhsan; Sulistiono, Budi; Alfarauq , Farkhan Abdurochim (PURBAWIDYA, 2024)
The purpose of this study is to determine the meaning of incense in the pilgrimage tradition of the tomb of Sunan Gunung Jati. The method used is qualitative with the collection of interview data, observation, and documentation. Researchers went directly to the field to collect data. The result of this research is that incense is used in the tradition of tomb pilgrimage Sunan Gunung Jati Cirebon is interpreted as fragnance and solemnity worship symboland intercedes with Allah SWT which is believed to be able to penetrate to the seventh heaven. Incense has a meaning depending on the pilgrim or the wearer including its purpose and background which is generally used to create a solemn atmosphere when praying. Incense is not obligatory for general pilgrims and is only used at certain times and places.